MO553INSIDE ANEMIA OF CKD: MICROSIMULATION MODELLING OF THE FUTURE COST BURDEN OF ANAEMIA OF CKD IN CANADA. (29th May 2021) - Retat, Lise; Webber, Laura; Garcia Sanchez, Juan Jose; Cabrera, Claudia; Grandy, Susan; Rao, Naveen; Bhatt, Purav; Wong, Deborah; Parackal, Anna; Wish, Jay; Tangri, Navdeep
Abstract: Background and Aims: Anaemia is a common complication in patients with chronic kidney disease (CKD). Prevalence of anaemia increases with CKD severity and ranges from 17% in patients with stage 3 disease to over 50% in patients with stage 5 CKD who are not on dialysis. Anaemia of CKD is associated with increased mortality, cardiovascular complications, reduced quality of life and increased use of healthcare resources. Mathematical modelling based on robust epidemiological and clinical data is a useful approach for predicting the future burden of disease, which is important for health service planning. This analysis uses a microsimulation model, Inside ANEMIA of CKD, to project the economic burden of anaemia of CKD in Canada from 2020 to 2025. Method: A virtual cohort representing the Canadian population was created within the Inside ANEMIA of CKD microsimulation model framework, using Canadian demographics and epidemiological data drawn from Statistics Canada and a provincial renal database. In the cohort, virtual individuals were ascribed an age–sex-stratified CKD status (defined by estimated glomerular filtration rate and albuminuria levels, as per international guidelines) and anaemia status (defined as mild, moderate or severe based on haemoglobin level, as per WHO criteria) based on Canadian prevalence data. Key comorbidities (type 2 diabetes, heart failure and hypertension) were also assigned, reflecting Canada-specific population statistics. Incidence rates for acute kidney injury and cardiovascular complications (heart failure, myocardial infarction and stroke) were drawn from the literature. Costs related to CKD, anaemia of CKD and associated complications were taken from Canadian government sources and the literature, and are shown in Canadian dollars (C$). Results: Preliminary results show that, in Canada, the number of individuals with anaemia of CKD is projected to increase by approximately 0.8 million between 2020 and 2025 (from 1.8 million to 2.6 million). Annual healthcare costs for patients with anaemia of CKD are projected to increase by 17% by 2025 (from C$19.3 billion to C$22.5 billion). Between 2020 and 2025, the costs associated with cardiovascular complications in patients with anaemia of CKD are projected to increase by 28% for heart failure (from C$1.13 billion to C$1.45 billion), 26% for myocardial infarction (from C$0.83 billion to C$1.05 billion) and 29% for stroke (from C$0.99 billion to C$1.29 billion). Conclusion: Inside ANEMIA of CKD is the first microsimulation model to project the economic burden of anaemia of CKD in Canada. Based on the modelling projections, the increase in the number of individuals with anaemia of CKD over the next 5 years will be accompanied by a parallel increase in associated healthcare costs and a marked rise in the cost of cardiovascular complications. Evidence-based therapies for anaemia of CKD that lower cardiovascular complications are needed to reduce the economic burden on healthcare services.